Kadar Glukosa Darah dan Tekanan Darah pada Anggota PROLANIS di Puskesmas Somagede Kabupaten Banyumas - Khafifah Leni Ashary (Poltekkes Kemenkes Semarang, 2019)
Health problems are affected by several factors, including lifestyle, diet, work environment factors, exercise, and stress. Changes in lifestyle can lead to an increase in the prevalence of degenerative diseases such as coronary heart disease, diabetes mellitus (DM), obesity, and high blood pressure. Risk factors that will occur due to increasing age include blood circulation disorders such as hypertension, blood vessel disorders, DM, and disorders of the joints. The purpose of this study was to determine the correlation between blood glucose levels and blood pressure in prolanis (Chronic Disease Management Program) members. The type and design of this study used an Analytical Observational design and a Cross Sectional design. The population in this study was 71 people with a sample of 35 respondents. The data in this study were secondary data obtained from data on blood glucose levels and blood pressure of prolanis members of the Somagede Public Health Care Center. The results of statistical tests showed that 11 people (31%) had high blood glucose levels, 18 people (52%) had normal blood glucose levels, and 6 people (17%) had low blood glucose levels. In addition, of these respondents, it was found that 11 people (31%) had high blood pressure, 24 people (63%) had normal blood pressure, and 2 people (6%) had low blood pressure. The analysis with the Pearson test showed that the value of p = 0.728, which means that H0 was accepted. Thus, there is no relationship between glucose levels and blood pressure in Prolanis members of the Somagede Public Health Care Center, Banyumas Regency. The null correlation between blood pressure and glucose levels might be because of the respondents' ability to control glucose levels, hence there are no complications that can increase blood pressure values.